MENGENAL KARAKTER TANAMAN ALFALFA (Medicago sativa L.) - Renan Subantoro (MEDIAGRO, 2009)
Alfalfa in Arab Ianguage have meaning as "Father  from all food" trusted as functioning crop to heal various disease. Factor influencing growth of alfalfa crop is internal and eksternal factor. Inhibitor factor growth of alfalfa crop do not only land  :  land, water, temperature, and light  intencity, and also weeds  factor. Study in this article use literature study method from various source of research result and book which have been done by writer. The crop Alfalfa (Medicago Sativa L) having various benefit from farmakologi, ecology, and  forage  aspect.  The growth  of  Crop Alfalfa (  Medicago Sativa L)  very influenced by internal factor which cover the nature of genetis for example including crop type having Calvin C3 type cycle and eksternal factor covering land ; land, water, air, light, pest & disease and weeds.